Reconstructing the Earth’s Social Ecosystem through Socio-Ecological Inquiry in the Climate Crisis Era - Mardikaningsih, Rahayu (Bulletin of Science, Technology and Society, 2025)
This study investigates the evolving structure of the Earth’s social ecosystem by analyzing the intersection between sociological systems and ecological forces in the context of climate disruption. It argues that environmental transformation is not merely a natural occurrence but a socially constructed and politically mediated process. Drawing from literature in environmental sociology, political ecology, and critical theory, the study traces how governance systems, economic models, cultural narratives, and technological infrastructures reinforce environmental degradation while simultaneously shaping social inequality. The analysis highlights how fragmented institutions, market-based ecological approaches, and extractivist logics sustain the conditions that generate climate vulnerability. It also explores how climate-induced displacement, contested environmental discourses, and uneven access to green technologies contribute to the reconfiguration of identity, agency, and justice in a warming world. By integrating theoretical insights from diverse disciplines, the study develops a comprehensive framework to interpret socio-ecological transformation. It emphasizes the need to move beyond disciplinary silos to understand the dynamics that condition both crisis and response. The findings contribute to a growing body of scholarship that advocates for interdisciplinary and critical approaches to environmental inquiry and offers pathways for equitable and resilient futures.